2018
DOI: 10.1039/c7ra12768e
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated graphene oxide/Nafion composite membranes for high temperature and low humidity proton exchange membrane fuel cells

Abstract: Iron oxide (Fe 3 O 4 ) nanoparticles anchored over sulfonated graphene oxide (SGO) and Nafion/Fe 3 O 4 -SGO composites were fabricated and applied as potential proton exchange membranes in proton exchange membrane fuel cells (PEMFCs) operated at high temperature and low humidity. Fe 3 O 4 nanoparticles bridge SGO and Nafion through electrostatic interaction/hydrogen bonding and increased the intrinsic thermal and mechanical stabilities of Nafion/Fe 3 O 4 -SGO composite membranes. Nafion/Fe 3 O 4 -SGO composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 66 publications
(80 reference statements)
3
137
0
Order By: Relevance
“…Thus, the characterization of morphology variation owing to the composition with inorganic pillar materials is crucial to the understanding of composite membranes. Many groups reported that the water uptake and proton conductivity increased because the hydrophilic ionic cluster network changes and the hygroscopic characteristics are improved by the sulfonized fillers materials . Lee et al studied the proton conductivity of SPAEK block copolymer membranes with a controlled F‐oligomer length bearing a pendant diphenyl unit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the characterization of morphology variation owing to the composition with inorganic pillar materials is crucial to the understanding of composite membranes. Many groups reported that the water uptake and proton conductivity increased because the hydrophilic ionic cluster network changes and the hygroscopic characteristics are improved by the sulfonized fillers materials . Lee et al studied the proton conductivity of SPAEK block copolymer membranes with a controlled F‐oligomer length bearing a pendant diphenyl unit.…”
Section: Introductionmentioning
confidence: 99%
“…The SGO increased the number of –SO 3 H groups per cluster volume domain, and Fe 3 O 4 induced the hydrogen bonding networks between the –SO 3 H groups. Accordingly, the water uptake, ion exchange capacity, and proton conductivity of the composite membrane increased owing to these changes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEMFC offers many advantages, such as high efficiency, silent operation, zero greenhouse-gas emission, and most importantly, high energy density. [4][5][6][7][8][9] Most of the aforementioned voltage drops are difficult to calculate, because some model parameters, such as the internal current (I int ), exchange current density (I o ), charge-transfer coefficient (α), and maximum limiting current (I lim ) for a PEMFC vary with ambient temperature and PEMFC loading conditions. 1,2 In PEMFC systems, hydrogen is supplied to the anode while ambient oxygen is supplied to the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, Si, Ti, Zr, and phosphonate functionalized CNT are commonly used for modification of PEM . Recently, carbon nanomaterials (MWCNTs and fullerene) with sulfonic acid groups have been widely used in the fabrication of composite membranes . Liu et al .…”
Section: Introductionmentioning
confidence: 99%